2005
DOI: 10.1007/s10549-004-2624-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Type plasminogen activator (tPA) in breast cancer: relationship with clinicopathological parameters and prognostic significance

Abstract: The results of the present investigation indicate that low intratumoral tPA levels are associated with aggressiveness and poor prognosis in breast cancer patients. However, the study suggests that tPA levels do not predict response to systemic adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Nevertheless, there are several unknown aspects on the role of HA in breast cancer. Thus, it is remarkable that in the present study we found, in addition to the finding of a positive relationship between HA and ER, a unexpected positive relationship between HA content and those of well-known estrogen-inducible proteins in breast cancer cells, such as PR [44], pS2 [45,46], tPA [47][48][49], which are also associated with a good prognosis in breast cancer [50][51][52][53][54][55][56]. These findings led us to consider that the estrogens might to modulate the HA expression in breast cancer.…”
Section: Discussionsupporting
confidence: 61%
“…Nevertheless, there are several unknown aspects on the role of HA in breast cancer. Thus, it is remarkable that in the present study we found, in addition to the finding of a positive relationship between HA and ER, a unexpected positive relationship between HA content and those of well-known estrogen-inducible proteins in breast cancer cells, such as PR [44], pS2 [45,46], tPA [47][48][49], which are also associated with a good prognosis in breast cancer [50][51][52][53][54][55][56]. These findings led us to consider that the estrogens might to modulate the HA expression in breast cancer.…”
Section: Discussionsupporting
confidence: 61%
“…One study showed that tPA expression in breast cancer is not associated with the malignant or benign state [52]. Another report states that low intratumoral tPA expression levels correlate with aggressiveness and poor prognosis for breast cancer patients [53]. Irrespective of these reports, increased PDGF-C expression and serine protease-mediated proteolytic activation of PDGF-C in human breast carcinoma MCF7 cells resulted in fibroblast migration in a paracrine manner as well as increased MCF7 cell proliferation and anchorage independent growth in an autocrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies reporting overexpression of some genes known to be associated with invasiveness and aggressiveness in estrogen negative tumors e.g. HER-2 neu, EGF, mutant P53 [27,28] High uPA (urokinase plasminogen activator) and type 1 plasminogen activator (PAI-1) was found to be associated with shorter recurrence-free survival and ER and PgR negativity [29]. Rodrigues et al reported that Cathepsin D expression was higher in ER and PgR-positive than in hormone receptor negative tumors [30].…”
Section: Discussionmentioning
confidence: 99%